Lipopolysaccharide exacerbates chronic restraint stress-induced neurobehavioral deficits: Mechanisms by redox imbalance, ASK1-related apoptosis, autophagic dysregulation. (December 2021) - Kwatra, Mohit; Ahmed, Sahabuddin; Gangipangi, Vijaya Kumar; Panda, Samir Ranjan; Gupta, Nitika; Shantanu, P.A.; Gawali, Basveshwar; Naidu, V.G.M.
Abstract: Major depressive disorder (MDD) is the foremost leading psychiatric illness prevailing around the globe. It usually exists along with anxiety and other clinical conditions (cardiovascular, cancer, neurodegenerative diseases, and infectious diseases). Chronic restraint stress (RS) and LPS-induce neurobehavioral alterations in rodent models however their interaction studies in association with the pathogenesis of MDD are still unclear. Therefore, the current study was aimed to investigate the LPS influence on chronic RS mediated redox imbalance, apoptosis, and autophagic dysregulation in the hippocampus (HIP) and frontal cortex (FC) of mice brain. Male Balb/c mice were exposed to 28 days consecutive stress (6h/day) with a single-dose LPS challenge (0.83 mg/kg, i.p.) on the last day (Day 28). In addition, we also carried out separate study to understand physiological relevance, where we used the DSS (dextran sulfate sodium), a water soluble polysaccharide (negatively charged) and studied its influence on RS induced neurobehavioral and certain neurochemical anomalies. The obtained results in RS and RS + LPS animal groups showed significant immune dysfunction, depleted monoamines, lowered ATP & NAD level, elevated serum CORT level, serum and brain tissues IL-1β/TNF-α/IL-6, SOD activity but reduced CAT activity. Furthermore, the redox perturbation was found where significantly upregulated P-NFκB p65, Keap-1, Prx-SO3 and downregulated Nrf2, Srx1, Prx2 protein expression was seen in RS + LPS mice. The apoptosis signaling (P-ASK1, P-p38 MAPK, P-SAPK/JNK, cleaved PARP, cleaved Caspase-3, Cyto-C), autophagic impairment (p62, LC3II/I) were noticed in HIP and FC of RS and RS + LPS grouped animals. Our new findings provide a complex interplay of chemical (LPS) and physical (RS) stressors where both single dose LPS challenge and 3% DSS in drinking water (for 7 days) exaggerated chronic RS-induced inflammation, lowered redox status, increased apoptosis and dysregulated autophagy leading drastic neurobehavioral alterations in the mice. Graphical abstract: Possible hypothetical events of LPS or DSS exacerbation of chronic Restraint stress induced depression-anxiety like behavior via microglia activation, surplus generation of oxido-nitrosative stress (ROS, H2 O2 ), neuroinflammation leads to interrupted redox balance, impaired autophagy (p62, LC3II/I), activated Apoptosis signaling (P-ASK1, P-p38 MAPK, P-SAPK/JNK, cleaved PARP-1, cleaved Caspase-3) in hippocampus and frontal cortex of mice. Image 1 Highlights: Single-dose LPS (0.83 mg/kg) aggravates chronic stress (168h; 6h per day for 28 consecutive days)-induced depressive-anxiety like behavior. Higher SOD, lower CAT activity and reduced ATP/NAD level directs energy crisis that perturb redox homeostasis thereby antioxidant axis. LPS exacerbates the chronic restraint stress induced autophagic dysfunction and enhanced apoptotic signaling cascade.